Emisiones de contaminantes primarios de Electro-Oriente y su efecto en la salud ambiental de los moradores de la zona Iquitos 2022 - Gatica Saboya de Macedo, Leticia (2024)
The objective of this research work was to determine the amount of primary pollutants emitted by the Iquitos thermal plant and relate it directly to the environmental health of the residents of the Electro Oriente environment; The problem being that these generators release in their operation, effluents, noise and emissions of pollutants, the latter are emitted into the atmosphere generating atmospheric pollution, these pollutants are: Carbon monoxide (CO), Sulfur oxide (SOx), Nitrogen oxides (NOx), Hydrocarbons (HC), particulate matter and Carbon dioxide (CO2) that constitute the main primary pollutants, causing negative effects on the health of the population, especially the residents who live around the plant. Electro East. As a hypothesis, the emission of primary polluting gases expelled by Electro Oriente influences the environmental health of the residents of the Electro Oriente environment. The investigation shows that there is a direct correlation between Carbon Monoxide (CO) vs. Environmental health indicator Eye conditions with r = .427 and rs = .417, statement valid up to 95% confidence, the other indicators such as Nitrogen Oxide (NOx), Sulfur Oxide (SOx), Hydrocarbons (HC) and PM10 particulate elements, although it is true there is a correlation with the indicators: respiratory conditions and eye conditions, but they are not significant.